ACUTE SEVERE HYPONATRAEMIA IN A PATIENT WITH RIGHT EYE PTOSIS - L, Jo Anne; S, Ruben; S, Ruben; I, Aznita (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Hyponatraemia is a common electrolyte imbalance in oncology. Syndrome of inappropriate anti-diuretic hormone secretion (SIADH) contributes to approximately 30% of cases. However, it remains a diagnosis of exclusion. In oncology, other possible contributing causes include reduced sodium intake, gastrointestinal and renal losses, chemotherapy and radiotherapy. However, for hyponatraemia in head and neck tumours, pituitary or hypothalamic involvement needs to be ruled out. We report a case of severe hyponatraemia and complex ophthalmoplegia in a patient with nasopharyngeal carcinoma (NPC) as a presentation of pituitary extension. The clinical records of a patient who was diagnosed with NPC were reviewed. CASE A 43-year-old gentleman presented with double vision, headache and weight loss for 2 months. It was associated with right third and sixth cranial nerve palsies, as well as left submandibular lymphadenopathy. Computerized tomography scan and lymph node biopsy confirmed the diagnosis of nasopharyngeal carcinoma. Prior to commencement of chemotherapy, he also presented with acute severe hyponatraemia which was resistant to supportive treatment. Urine osmolality and serum osmolality pointed toward SIADH, but the patient was not responsive to fluid restriction and hypertonic saline correction. Pituitary gland function tests and magnetic resonance imaging subsequently confirmed pituitary extension of the NPC causing central hypocortisolaemia with concomitant SIADH. Hyponatraemia was successfully treated with oral hydrocortisone and oral sodium chloride. CONCLUSION This case study illustrates important presentations of NPC progression. Complex ophthalmoplegia and hyponatraemia are both warning signs of intracranial NPC extension.